The Dynamical Model of Zika Transmission from Mother to Baby - Puntipa Pongsumpun; Puntani Pongsumpun (My University, 2023)
Zika virus is transmitted to human by biting of infected Aedes mosquito or having sex with an infected person. This disease can be transmitted between mother and baby. This paper described the transmission of Zika virus by using the transmission model. We analyze the transmission model by using standard dynamical analysis. The equilibrium points are found. The local stabilities are determined. Numerical solutions are shown. The way for reducing the transmission of Zika virus is suggested.
Keywords: Mosquito-borne diseases and control; Viral Infections and Vectors; COVID-19 epidemiological studies